Analisis Sentimen Review Film Berbahasa Inggris Dengan Pendekatan Bidirectional Encoder Representations from Transformers - Cindy Alifia Putri (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Sentiment Analysis is the process of analyzing a person's opinion or attitude. Sentiment analysis is used to get the results of an analysis of various opinions or judgments of someone in providing comments or opinions. In this study, the authors conducted a sentiment analysis of film reviews using the cornell edu dataset from pabo for film reviews with a classification process using the Bidirectional Encoder Representations from Transformers (BERT) algorithm that performs fine tuning with some layer for classification. From this study, obtained the accuracy of the results calculated by the sparse categorical cross entropy of 73%.